Teachers’ Feedback on the Development of Virtual Speaking Buddy (VirSbud) Application - Radzuwan, Ab Rashid; Saiful Bahri, Mohamed; Syadiah Nor, Wan Shamsuddin; Mohd Fazry, A.Rahman (2017)
This study aims at identifying the ideal characteristics of a virtual speaking buddy (VirSbud), as perceived by the teachers, so that the current VirSbud application can be further developed to meet the users’ expectation. Employing a qualitative approach, an in-depth group interviews was conducted with five English language teachers teaching in Standard Three (nine-year-old pupils). Prior to the interview, the teachers used the application as a teaching aid for eight weeks. The interview reveals the ideal characteristics of an application for virtual speaking buddy. The teachers expected a more sophisticated application which enables online participation, two different interfaces accessible by learners and teachers, looping in the prompts given to the learners, and the use of voice recognition which enables automatic response to the learners. The findings point towards the need of semi-formal learning, instead of formal and informal learning, in developing learners’ speaking skills with the teachers being virtually present at a distance.